LOAD PROFILE OF WORKFORCE USING WESTINGHOUSE METHOD IN WAREHOUSE WORK SYSTEM - Sonny Aji; Aina Nindiani (Industry Xplore, 2023)
Workers play a crucial role in a company, and their workload significantly influences productivity. This research was conducted in a manufacturing company, specifically in the Warehouse Department (storage section), due to indications of low productivity. The research objective was to analyze the workload profiles of workers in the storage section of the manufacturing company’s warehouse. The analysis was conducted using the Westinghouse method, which considers skill, effort, condition, and consistency in analyzing work time. Cycle time to standard time was calculated considering rating factors and allowances. The research results revealed that the four workers in this section experienced workload levels of 68% for Worker 1, 28% for Worker 2, 57% for Worker 3, and 50% for Worker 4. Overall, the workers exhibited an underloaded workload profile. The highest underload was observed in Worker 2, indicating the lowest productivity among the four workers. Based on these findings, it is recommended to enrich the job tasks for workers in the warehouse or consider transferring them to other departments that require additional workforce to improve the current work system in the warehouse. Keywords: load profile; warehouse; Westinghouse; workload; work system